Chemical approaches to inhibitors of isoprenoid biosynthesis: targeting farnesyl and geranylgeranyl pyrophosphate synthases. Issue 18 (10th February 2017) - Merino, Pedro; Maiuolo, Loredana; Delso, Ignacio; Algieri, Vincenzo; De Nino, Antonio; Tejero, Tomas
Abstract : The chemical synthesis of farnesyl and geranylgeranyl pyrophosphate synthase inhibitors are surveyed. Abstract : Post-translational lipid modifications farnesylation and geranylgeranylation of proteins (protein prenylation) have been identified to mediate critical events in cancer, cardiovascular disorders, malaria and bone disorders like osteoporosis. To date eight compounds are commercialized for the treatment of bone disorders, and there are considerable efforts to develop selective small molecules that inhibit protein prenylation. This review summarizes the approaches currently employed to synthesize new inhibitors of isoprenoid biosynthesis. Bisphosphonates are mainly prepared through reaction of carboxylic acids with phosphorus reagents, Michael addition to tetraethylvinylidenebisphosphonate and alkylation of tetralkylmethyl bisphosphonate. Approaches to non-bisphosphonate derivatives include a variety of methodologies depending on the structure of the target compound.